Thunderstorm-Associated Asthma or Shortness of Breath Epidemic: A Canadian Case Report - AE Dennis Wardman; Dennis Stefani; Judy C MacDonald (Canadian Respiratory Journal)
Thunderstorm-associated asthma epidemics have been documented in the literature, but no Canadian experience has been reported. On July 31, 2000, a thunderstorm-associated epidemic of asthma or shortness of breath occurred in Calgary, Alberta. The Calgary Health Region investigated the event using diagnostic data from emergency departments, an urgent care medical clinic and patient interviews, in addition to bioaerosol counts, pollutant data and weather data reflecting atmospheric conditions at that time. On July 31, 2000 and August 1, 2000, 157 people sought care for asthma symptoms. The expected number of people to seek care for such symptoms in a 48 h period in Calgary is 17. Individuals with a personal or family history of asthma, allergies or hay fever who were not taking regular medication for these conditions and who were outdoors before the storm appeared to have been preferentially affected. A stagnant air mass the day before the thunderstorm may have resulted in declining bioaerosol concentrations, and the possible accumulation of spore and pollen reservoirs within mould and plant structures. The elevated bioaerosol concentrations observed on the day of the thunderstorm may be attributed to the sudden onset of high winds during the thunderstorm, which triggered a sudden release of spores and pollens into the atmosphere, which was probably responsible for the epidemic. Several pollutant levels slightly increased on the day of the storm and possibly also played a role in symptom development. It is unclear whether an atmospheric pressure drop contributed to the release of spores and pollens.